More of you : the fat girl's field guide to the modern world - Beck, Amanda Martinez (Broadleaf Books, 2022)
In More of You Amanda Martinez Beck gives fellow fat women who have been pushed to the margins of acceptance hard-won wisdom on how to thrive. This book will challenge the status quo, teaching readers to resist shame and guilt and instead to embrace their bodies, take up space, and learn to navigate the world in ways that allow them to flourish.